ENHANCING ENGLISH LANGUAGE PROFICIENCY THROUGH AI-SUPPORTED INTEGRATED SKILLS INSTRUCTION (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The rapid expansion of artificial intelligence (AI) has significantly transformed language education, especially in the teaching of English as a foreign language (EFL). While traditional instruction often isolates language skills, current pedagogical frameworks emphasize the importance of integrated skills development. This article explores how AI-supported tools can enhance learners’ proficiency by combining listening, speaking, reading, and writing within a unified instructional model. Drawing on recent research, the paper analyzes the pedagogical value of AI applications, their role in personalized learning, and their potential to increase learner autonomy and engagement. The study also examines challenges associated with AI integration, including technological limitations, teacher preparedness, and ethical considerations. Recommendations are provided for educators and institutions seeking to implement AI-driven, integrated skills instruction effectively.